Fenômenos relacionados a uma unidade de saúde mental: porta giratória e percepções de violências da equipe de enfermagem - Pereira, Pedro Guimarães (2024)
The study described the number of psychiatric rehospitalizations, presented the diagnoses coded according to the International Classification of Diseases - ICD-10 with the highest prevalence, and compared them with the revolving door phenomenon. It also detailed the types of violence, their manifestations, and the feelings expressed in the experiences and perceptions of nursing professionals when perpetrated by patient(s) with mental disorder(s) who were hospitalized in a Mental Health Unit in the municipality of Uberlândia.